2020
DOI: 10.3390/e22090953
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Reproducibility of Chaos Simulation

Abstract: An evergreen scientific feature is the ability for scientific works to be reproduced. Since chaotic systems are so hard to understand analytically, numerical simulations assume a key role in their investigation. Such simulations have been considered as reproducible in many works. However, few studies have focused on the effects of the finite precision of computers on the simulation reproducibility of chaotic systems; moreover, code sharing and details on how to reproduce simulation results are not present in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 102 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…It is worth noting here that as far as the numerical evaluation of the chaotic system in the transmitter and receiver ends is concerned, there are instances where errors can arise, that may lead to degradation of the design. Examples can include round-off errors that arise when a different error tolerance is chosen between transmitter and receiver, or errors that arise when a different integration step is chosen or different numerical methods are used to solve the system; see for example, discussions in the recent works [52][53][54]. This is one of the main obstacles that have so far held up the possible commercialization of chaos-based secure communications.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting here that as far as the numerical evaluation of the chaotic system in the transmitter and receiver ends is concerned, there are instances where errors can arise, that may lead to degradation of the design. Examples can include round-off errors that arise when a different error tolerance is chosen between transmitter and receiver, or errors that arise when a different integration step is chosen or different numerical methods are used to solve the system; see for example, discussions in the recent works [52][53][54]. This is one of the main obstacles that have so far held up the possible commercialization of chaos-based secure communications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for a chaotic dynamical system, calculated trajectories of computer-generated simulations obtained by means of different numerical algorithms (with single/double precision) and different time steps are mostly quite different. Naturally, such kind of nonreplicability/unreliability of chaotic solution has brought plenty of heated debates on the credence of the numerical simulation of chaotic dynamical system [35], and someone even made an extremely pessimistic conclusion that "for chaotic systems, numerical convergence cannot be guaranteed forever" [47]. In addition, it has been recently reported that "shadowing solutions can be almost surely nonphysical", which "invalidates the argument that small perturbations in a chaotic system can only have a small impact on its statistical behavior" [4].…”
Section: Introductionmentioning
confidence: 99%
“…But in fact, it is not 100% natural chaos, it is degraded chaos due to computational limitations. 2932 This can cause irreproducible and unreliable results, Nazaré et al 33 studied this topic.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] This can cause irreproducible and unreliable results, Nazare ét al. 33 studied this topic. As Ott et al 5 point out in their pioneering paper, any chaotic dynamic system can be controlled to be used by different purposes at different times.…”
Section: Introductionmentioning
confidence: 99%